2019
DOI: 10.1177/0954405419855874
|View full text |Cite
|
Sign up to set email alerts
|

Research on the optimal combination and scheduling method of crowdsourcing members in a cloud design platform

Abstract: Cloud design has become a potential emerging design service mode. More and more design service providers are clustered in a cloud design platform to become crowdsourcing members. Collaborative tasks published by the platform are usually performed by several crowdsourcing members, and the collaborative mode of crowdsourcing members is an asynchronous collaborative working mode. However, due to the variety of crowdsourcing members in terms of ability, time, and so on, how to combine crowdsourcing members into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…According to the result of average satisfaction degrees, each SQA was quantified by Eqs. (10)(11) into a polar form representation scheme including the importance and the performance indices, as shown in Table 9.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the result of average satisfaction degrees, each SQA was quantified by Eqs. (10)(11) into a polar form representation scheme including the importance and the performance indices, as shown in Table 9.…”
Section: 2mentioning
confidence: 99%
“…Given the protection of intellectual property rights, the role of crowdsourcing platforms have been discussed [23]. Chen et al [10] proposed an optimal combination and scheduling method to respond the challenge of allocating heterogeneous solvers to construct a rational crowdsourcing team. Wen and Lin [52] constructed an optimal fees structure of a crowdsourcing platform depending on the game-theoretic model.…”
mentioning
confidence: 99%
“…The encapsulation is expanded and strengthens the communication among models, achieve the reusability of the scheduling model, and improve the modeling efficiency. [38][39][40][41] As shown in Figure 1, in the knowledge domain, the knowledge component space description model includes the model knowledge, meta knowledge, and algorithm knowledge. Through the attribute modeling and knowledgeable interface, the model will be encapsulated as an independent knowledge unit for invoking.…”
Section: Inspirationmentioning
confidence: 99%
“…The earlier studies of cloud design, cloud simulation, cloud machining, and cloud threedimensional (3D) printing laid the foundation for cloud inspection. For example, Chen, et al demonstrated an innovative service model of the cloud design platform and proposed a method of crowdsourcing the optimal combination and scheduling of members to improve the efficiency of cloud design [11]. Zhang, et al proposed a cloud-based 3D printing service platform based on CMfg [12].…”
Section: Introductionmentioning
confidence: 99%